Association of N-Terminal Pro-brain Natriuretic Peptide With Volume Status and Cardiac Function in Hemodialysis Patients - Wang, Yaqiong; Cao, Xuesen; Yu, Jinbo; Zhang, Yongmei; Li, Xianzhe; Chen, Xiaohong; Zou, Jianzhou; Shen, Bo; Ding, Xiaoqiang (Frontiers in Cardiovascular Medicine, 2021)
Introduction: N-terminal-pro-brain natriuretic peptide (NT-pro BNP) is secreted by cardiomyocytes in cases of cardiac structure disorder and volume overload. However, the relationship between NT-pro BNP level and body fluid status in dialysis patients with reduced cardiac ejection function (EF) is uncertain. Therefore, we aimed to investigate this relationship. Methods: We enrolled patients who had been receiving hemodialysis for >3 months. Blood sample, transthoracic echocardiographic, and bioimpedance spectroscopy measurements were performed during a midweek non-dialysis day. The predictive value of NT-pro BNP in hemodialysis patients with volume overload was analyzed. Results: A total of 129 hemodialysis patients (74 men and 55 women; mean age: 59.4±13.0 years) were recruited. The average hemodialysis duration was 55.5 (23.9–93.4) months, the NT-pro BNP level was 4992 (2033–15807) pg/mL, and the value of overhydration was 2.68±0.19 (-1.9-12.2) L. The NT-pro BNP level was independently correlated with overhydration in both the LVEF ≥60% (β=0.236, P=0.044) and LVEF <60% (β=0.516, P=0.032) groups, even after adjustments for potentially confounding variables. In receiver operating characteristic curves of NT-pro BNP for predicting volume overload, the area under the curve was 0.783 (95% CI [0.688–0.879], P<0.001) and 0.788 (95% CI [0.586–0.989], P<0.001) in the LVEF ≥60% and LVEF<60% groups, respectively. Conclusions: NT-pro BNP is a predictive factor for volume overload in hemodialysis patients with or without EF declines.